2021
DOI: 10.3389/fphar.2021.746935
|View full text |Cite
|
Sign up to set email alerts
|

CBD Effects on Motor Profile and Neurobiological Indices Related to Glutamatergic Function Induced by Repeated Ketamine Pre-Administration

Abstract: Clinical evidence and experimental studies have shown the psychotomimetic properties induced by ketamine. Moreover, acute or chronic ketamine (KET) administration has been widely used for modeling schizophrenia-like symptomatology and pathophysiology. Several studies have reported the antipsychotic potential of cannabidiol (CBD), while there is limited information on the cannabidiol effect on KET-induced schizophrenia-like impairments. Therefore, the goal of the present study was to evaluate neuroplastic chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The finding of reduced pain sensitivity for the supraspinalrelated hot plate test but not the spinal-related tail flick test may be explained by a previous study that found higher Tat mRNA expression in the striatum compared to the spinal cord (Kronemer et al, 2017). For acute CBD exposure, no effects on pain sensitivity in Tat transgenic mice were found at any dose given (3, 10, 30 mg/kg), even though other studies demonstrated attenuation of pain sensitivity by acute CBD treatment of similar doses in preclinical rodent models of inflammatory pain (June et al, 2009;Ceccarelli et al, 2020) and neuropathic pain (Moran et al, 2013;Poulia et al, 2021). To our knowledge, cannabidiol's effects on pain have not been studied in PLWH and/or neuroHIV mouse models, including the Tat transgenic mouse model.…”
Section: Discussionmentioning
confidence: 88%
“…The finding of reduced pain sensitivity for the supraspinalrelated hot plate test but not the spinal-related tail flick test may be explained by a previous study that found higher Tat mRNA expression in the striatum compared to the spinal cord (Kronemer et al, 2017). For acute CBD exposure, no effects on pain sensitivity in Tat transgenic mice were found at any dose given (3, 10, 30 mg/kg), even though other studies demonstrated attenuation of pain sensitivity by acute CBD treatment of similar doses in preclinical rodent models of inflammatory pain (June et al, 2009;Ceccarelli et al, 2020) and neuropathic pain (Moran et al, 2013;Poulia et al, 2021). To our knowledge, cannabidiol's effects on pain have not been studied in PLWH and/or neuroHIV mouse models, including the Tat transgenic mouse model.…”
Section: Discussionmentioning
confidence: 88%
“…For CBD, the present study found that all three CBD doses (3, 10, 30 mg/kg) increased activity independent of Tat expression without affecting rotarod performance. Multiple preclinical studies have reported the lack of CBD effects on locomotor activity in non-diseased mice [121,122] and disease rodent models [123][124][125], including motor performance in the rotarod test [122,126], which is supported by a recent review on effects of cannabidiol on locomotor activity [127]. Even though we did not see differential effects of CBD based on Tat expression, a previous study reported reduction of hypolocomotion by chronic treatment of CBD via 5-HT1A receptors, and thus improvement in motor dysfunction caused by hepatic encephalopathy [128], which demonstrates CBD can increase locomotor activity as shown in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Fmr1 KO and WT rats were euthanized by decapitation under isoflurane anesthesia, their brains were immediately removed for dissection of the prefrontal cortex (PFC), the dorsal hippocampus (D. Hip), and the ventral hippocampus (V. Hip), and analyzed with immunoblotting [ 17 , 18 ]. Following electrophoresis, proteins were transferred onto a nitrocellulose membrane with a Bio-Rad CriterionTM Blotter with wired electrodes (wet transfer, 100 V for 45 min) according to the molecular weight of each protein tested.…”
Section: Methodsmentioning
confidence: 99%